2018
DOI: 10.1101/326405
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Parallel multimodal circuits control an innate foraging behavior

Abstract: SUMMARYForaging strategies that enable animals to locate food efficiently are composed of highly conserved behavioral states with characteristic features. Here, we identify parallel multimodal circuit modules that control an innate foraging state --local search behavior --after food removal in the nematode Caenorhabditis elegans. Two parallel groups of chemosensory and mechanosensory glutamatergic neurons that detect food-related cues trigger local search by inhibiting separate integrating neurons through a me… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 68 publications
0
21
0
Order By: Relevance
“…If AWC-mediated glutamatergic transmission inhibits temperature responses in AIA in starved animals, we would predict that blocking glutamatergic signaling from AWC would also be sufficient to restore negative thermotaxis upon starvation. Indeed, we found that knocking out the glutamate transporter eat-4 cell-specifically in AWC ( López-Cruz et al, 2019 ) resulted in robust negative thermotaxis behavior by starved animals ( Figure 3I ). These experiments suggest that upon prolonged starvation, increased AWC temperature responses inhibit AIA via glutamatergic signaling to disrupt negative thermotaxis via warming-uncorrelated regulation of reversals and turns.…”
Section: Resultsmentioning
confidence: 94%
See 4 more Smart Citations
“…If AWC-mediated glutamatergic transmission inhibits temperature responses in AIA in starved animals, we would predict that blocking glutamatergic signaling from AWC would also be sufficient to restore negative thermotaxis upon starvation. Indeed, we found that knocking out the glutamate transporter eat-4 cell-specifically in AWC ( López-Cruz et al, 2019 ) resulted in robust negative thermotaxis behavior by starved animals ( Figure 3I ). These experiments suggest that upon prolonged starvation, increased AWC temperature responses inhibit AIA via glutamatergic signaling to disrupt negative thermotaxis via warming-uncorrelated regulation of reversals and turns.…”
Section: Resultsmentioning
confidence: 94%
“…Similar HisCl1-mediated silencing of the ASI bacteria-sensing neurons ( Gallagher et al, 2013 ) had no effect on the expected negative thermotaxis behaviors ( Figure 2—figure supplement 1C ). As an independent verification, we silenced AWC via cell-specific expression of the light-gated anion channelrhodopsin GtACR2 ( Govorunova et al, 2015 ; López-Cruz et al, 2019 ). Optogenetic silencing of AWC during the assay was again sufficient to restore negative thermotaxis bias in starved animals ( Figure 2B ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations